Influence of Contract Management on Performance of Public Hospitals in Nairobi City County, Kenya - Karoki, Anne Wanjiru; Mwangangi, Dr. Patrick (International Journal of Supply Chain and Logistics, 2020)
Purpose: The study sought to establish the influence of contract management on performance of public hospitals in Nairobi City County, Kenya. Methodology: This study employed descriptive research design. The study reviewed both theoretical and empirical literature and then proposed the research methodology that addressed the gaps identified in literature as well as to validate the statistical hypotheses. The researcher preferred this method because it allows an in-depth study of the subject. The study population was all public hospitals in Kenya. To gather data, structured questionnaire was used to collect data from 76 staff in procurement, administration and finance departments from the four largest public hospitals in Nairobi County; Kenyatta National Hospital, Mama Lucy Kibaki Hospital, Mbagathi District Hospital and Pumwani Maternity. The target population was all public hospitals in Nairobi City County. The target population was first stratified then using simple random sampling among the four strata, select the samples. The study combined two methods in its data collection that is, questionnaires and key informant interviews. After data collection, quantitative data was coded using Statistical Package for Social Science (SPSS) version 20. Data was analyzed through descriptive statistical methods such as means, standard deviation, frequencies and percentage. Inferential analysis was used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable. Findings: R square value of 0.647 means that 64.7% of the corresponding variation in performance of public hospitals in Kenya can be explained or predicted by (contract planning, monitoring and evaluation, contractor relationship management and dispute resolution) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.647), p=0.000 <0.05). The findings of the study concluded that contract planning, monitoring and evaluation, contractor relationship management, dispute resolution have a positive relationship with performance of public hospitals in Kenya. Unique contribution to theory, practice and policy: The study recommended that public institutions should embrace contract management practices so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained.